2017
DOI: 10.1007/s00348-017-2391-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of whistling in vertical corrugated pipes by liquid addition

Abstract: (FIVs) can occur, caused by an interaction between an acoustic pipe resonance and the unsteady shear layers spanning the corrugations. Under certain conditions, these FIVs result in the production of high-amplitude tonal noise (also known as whistling). This is not only inconvenient, but can lead to damage of equipment, failure of piping systems, and hazardous situations. This study focuses on whistling attenuation by liquid addition to vertical corrugated pipe flow, and the identification of the mechanisms be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It is anticipated that the direction of gravity will have a strong effect on the obtained results. In a previous study, van Eckeveld et al (2017) found that the flow direction with respect to the gravity has significant consequences for the liquid cavity filling behavior. The liquid filling ratio is considerably higher for downward directed flow.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is anticipated that the direction of gravity will have a strong effect on the obtained results. In a previous study, van Eckeveld et al (2017) found that the flow direction with respect to the gravity has significant consequences for the liquid cavity filling behavior. The liquid filling ratio is considerably higher for downward directed flow.…”
Section: Discussionmentioning
confidence: 96%
“…Ansari and Arzandi (2012) for horizontal channels with ribs. Recently, new attention was given to two-phase flows in corrugated pipes in the framework of the mitigation of flowinduced vibrations in these pipes ( Belfroid et al, 2013;van Eckeveld et al, 2017 ). The presence of liquid was found to reduce, and eventually mitigate, flow-induced noise.…”
Section: Introductionmentioning
confidence: 99%